O choro e suas interações com a banda do corpo de bombeiros do Rio de Janeiro: uma via de mão dupla nas décadas de 1870 a 1940 - Nolasco Junior, Sebastião (2017)
This study aimed to research the interactions of the choro with the Banda do Corpo de Bombeiros do Rio de Janeiro (BCBRJ), conducted by Anacleto de Medeiros and Albertino Pimentel in the late nineteenth and early twentieth centuries (1870s to 1940s), observed through the legacies left for the history of the genre. Aiming to investigate the stylistic peculiarities of the choro practiced during the period cited above and considering its relation with the arrangements and other peculiarities of the music performed by the BCBRJ, we sought to explore four categories of interactions that occurred with the choro and the BCBRJ. The approach of the first category verified that there was an intense traffic of musicians from the BCBRJ to the choro environment, and vice versa; the focus of the second one evidenced the circularity of the repertoire that was interpreted by the BCBRJ and the choro groups, revealing that part of it was composed by the chorões members of the band; the third category revealed that the circularity also happened through the appropriation by the choro groups of wind instruments, strong characteristic of the band; as for the fourth category, it dealt with the confluences of stylistic aspects that permeated the compositions and arrangements executed by the BCBRJ and the choro groups, through the analysis of selected works from their repertoires for this purpose. The result achieved with the approach of these four categories confirmed that there were interactions configured as a two-way street between the two musical formations, important for the consolidation of the choro as a proper musical genre. On the other hand, we always tried to emphasize that such interactions came from the reformed sociocultural scenario in Rio de Janeiro, which sought to become modern, where different cultural dimensions marked their spaces, symbolically demonstrating struggles of forging representations of identity processes. The practice of the music through this two-way street integrated this context, marking the identity space and the circulation of chorões and band members in the scenario and period in question.